Severe problem of macrolides resistance to common pathogens in China - Li, Jialin; Liu, Lesen; Zhang, Hua; Guo, Jing; Wei, Xiaoling; Xue, Min; Ma, Xiang (Frontiers in Cellular and Infection Microbiology, 2023)
With the widespread use of macrolide antibiotics in China, common pathogens causing children’s infections, such as Streptococcus pneumoniae, Streptococcus (including Group A streptococcus, Group B streptococcus), Staphylococcus aureus, Bordetella pertussis, and Mycoplasma pneumoniae, have shown varying degrees of drug resistance. In order to provide such problem and related evidence for rational use of antibiotics in clinic, we reviewed the drug resistance of common bacteria to macrolides in children recent 20 years.